Nevus sebaceus with basal cell carcinoma, poroma, and verruca vulgaris - Ali Fuat Cicek; Andac Aykan; Abdulkerim Yapici; Mehmet Gamsizkan; Serdar Ozturk; Murat Demiriz (Wolters Kluwer Medknow Publications, 2015)
Nevus sebaceus (NS) is a congenital, benign, hamartomatous lesion and it is possible to see several benign or malignant tumors accompanying it. One of these is the poroma, which is very rare, and has only been reported twice before, in the English literature. In this paper, we presented two new cases of NS. One of them was a 40-year-old male who presented with a congenital skin lesion on his temporoparietal region. This lesion was composed of four different lesions, including NS, poroma, basal cell carcinoma (BCC), and verruca vulgaris. The second patient was a 41-year-old male presenting with a yellow-brown patch on the scalp. This lesion was comprised of NS and BCC. In addition to these presentations, we discussed the differential diagnosis between BCC and trichoblastoma, both of which are likely to be seen with NS. For this purpose, we recommended an immunohistological panel, which may be useful for differentiating these two morphologically similar lesions.